PEMBUATAN BRIKET ENERGI TINGGI DARI CANGKANG KAKAO YANG DIAKTIVASI DENGAN MIKROWAVE - I Nyoman Sudiana; L. Lestari; M.Z. Firihu; Y.A. Koedoes; G.E. Sandra; Y. Biringgalo; L. Arfad; P.A. Setyo; E. Safitri (Universitas Halu Oleo, 2017)
Charcoal briquettes from cocoa shell have been producting. Composition of glue and cacao shell as well as their microstructure (pores and grains) are optimized in order to obtain briquettes with high calor energy. The optimation of microstructure is performed by microwave activation. High glue content affect to the briquette’s moisture. The composition of glue material and cocoa shell charcoal which give highest calor energy found in this research is 5:95 %. From microstructure evaluation we found that at the pores diameter of 552 micrometer in average and grain size of 152 micrometer, the average energy of activated charcoal cocoa shell is 10,321 kkal/kg.Keywords: Cocoa shell, briquettes, calor energy, charcoal, microstructure, microwave